2007
DOI: 10.2176/nmc.47.47
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Intracranial Hematoma Enlargement in Patients Undergoing Hemodialysis

Abstract: The factors associated with hematoma enlargement were analyzed in 24 patients, 16 males and eight females aged 46 to 77 years (mean 58 years), undergoing chronic hemodialysis who were admitted to our hospital with intracerebral hemorrhage between 1994 and 2003. Computed tomography demonstrated hematoma enlargement in eight patients after admission. Age, sex, duration of dialysis, time interval between onset and admission, site of hemorrhage, and blood pressure on admission were not significantly different betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 13 publications
0
13
1
Order By: Relevance
“…In cases in which the intraventricular bleeding was concurrently present, the amount of initial bleeding was significantly greater, and the mortality was approximately two times higher. [16,17] According to a study which was conducted in 41 patients with stroke, 31 had a cerebral hemorrhage. Cerebral hemorrhage was developed approximately ten years earlier in the dialysis group than the non-dialysis group.…”
Section: Discussionmentioning
confidence: 99%
“…In cases in which the intraventricular bleeding was concurrently present, the amount of initial bleeding was significantly greater, and the mortality was approximately two times higher. [16,17] According to a study which was conducted in 41 patients with stroke, 31 had a cerebral hemorrhage. Cerebral hemorrhage was developed approximately ten years earlier in the dialysis group than the non-dialysis group.…”
Section: Discussionmentioning
confidence: 99%
“…35 Other investigators have applied various shape definitions in studies of amyloid and hypertensive bleeds (round, lobular, or irregular), 36 warfarin-related hemorrhages (round to ellipsoid with smooth margins, irregular with frayed margins, multinodular to separated), 28 and in an analysis of ICH growth predictors in a small study of patients undergoing hemodialysis (round and irregular groups). 37 In contrast, we used a scale that was validated by testing within-and between-observer agreement, studied patients at relatively homogeneous times after onset of symptoms, and used standardized growth definitions. These scales are the first attempt to visually categorize the spectrum of shape and density variation in ICH morphology.…”
mentioning
confidence: 99%
“…In this study, we showed that the mortality rates were not significantly different for the EHD and CPD patients. In addition, our patients had a relatively lower mortality rate (total mortality 27.9%) than other series (mean mortality 62.1%, range 43.8–67.3%) [7,8,10,11,16,17,18]. The mean outcome score was 3 in the CPD and 2 in the EHD groups, respectively.…”
Section: Discussionmentioning
confidence: 47%
“…The prognosis of ICH in chronic dialysis patients is especially poor. The 30-day mortality rate has been reported to be as high as 67.3% (range 43.8–67.3%) [7,8,10,11,16,17,18]. The total 30-day mortality rate of our patients was 27.9%.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation